2014
DOI: 10.1097/bpo.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Fibular Lengthening for the Management of Translational Talus Instability in Hereditary Multiple Exostoses Patients

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…The femoral neck-shaft angle was defined as the angle between the axis of the femoral neck passing through the center of the femoral head and the axis of the femoral shaft [ 13 ], and an increased femoral neck-shaft angle was defined as an increase of ≥10° in the femoral neck-shaft angle of the affected limb compared with the contralateral limb. The tibiofemoral angle was defined as the angle formed by the axis of the femur and the axis of the tibia [ 14 ], whereas the ankle valgus angle was regarded as the angle between the axis of the tibial shaft and the tibial plafond line [ 15 ]. We also examined the effect of an increased femoral neck-shaft angle on FO.…”
Section: Methodsmentioning
confidence: 99%
“…The femoral neck-shaft angle was defined as the angle between the axis of the femoral neck passing through the center of the femoral head and the axis of the femoral shaft [ 13 ], and an increased femoral neck-shaft angle was defined as an increase of ≥10° in the femoral neck-shaft angle of the affected limb compared with the contralateral limb. The tibiofemoral angle was defined as the angle formed by the axis of the femur and the axis of the tibia [ 14 ], whereas the ankle valgus angle was regarded as the angle between the axis of the tibial shaft and the tibial plafond line [ 15 ]. We also examined the effect of an increased femoral neck-shaft angle on FO.…”
Section: Methodsmentioning
confidence: 99%
“…The first reports have promising results 79,80. Fibular lengthening has also been evaluated in the prevention and initial correction of ankle valgus deformities and talus instability with optimal results 81. Valgus deformities of the proximal femur could be corrected by several approaches with variable results 82.…”
Section: Treatmentmentioning
confidence: 99%
“…These interventions are often performed to prevent severe deformities, arthrosis and dysmetria. [17][18][19][20][21][22] In 2012 Goud et al evaluated pain and quality of life in a large cohort of patients with HME. The author found that 57 children (58%) participated in sports at the time of evaluation.…”
Section: Discussionmentioning
confidence: 99%